Towards a 15-minute city: A network-based evaluation framework. (February 2023) - Zhang, Shanqi; Zhen, Feng; Kong, Yu; Lobsang, Tashi; Zou, Sicong
Developing 15-minute cities, where people can access to living essentials within a 15-minute trip, has become a global effort. In addition to practical exercise, researchers have paid attention to the evaluation of 15-minute cities using home-based accessibility approaches. However, existing approaches do not account for human mobility, an important indicator of how people access and interact with urban amenities. In this study, we propose a novel network-based framework that assesses a 15-minute city considering human mobility patterns. We assume that there exists an optimal mobility network, which would maximize human mobility under the constraints of the current distribution of amenities. Locations where the provision of urban amenities does not match local needs are first identified based on the comparison between optimal mobility patterns and their actual counterparts. Built environment, demographic, and network structure factors that contribute to identified mismatch issues are then examined. The empirical study of Nanjing, China, suggests that the proposed framework could enable a dynamic evaluation of 15-minute cities and could provide important insights on policies and intervention strategies of planning and developing 15-minute cities.